2019
DOI: 10.1002/jcb.28491
|View full text |Cite
|
Sign up to set email alerts
|

A novel copper (II) complex activated both extrinsic and intrinsic apoptotic pathways in liver cancerous cells

Abstract: Recent advances have put fundamental focus on the application of copper (II) (Cu [II]) complexes as agents for fighting against cancer. To determine whether [Cu(L)(2imi)] complex as a novel Cu complex can induce apoptosis in HepG2 as cancerous cells and L929 as normal cells via extrinsic or intrinsic apoptotic pathways, both cell lines were treated for 24 and 48 hours at IC 50 concentrations of [Cu(L)(2imi)] complex. Then, the expression of some apoptosis-related genes including p53, caspase-8, bcl-2, and bax … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Therefore, based on these observations, ATRA combined with BDMC increased the ratio of Bak/Bcl-2 for leading to cell apoptosis. The Bax/Bcl-2 ratio was concerned with cell response to apoptotic signals (Rezaei et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…Therefore, based on these observations, ATRA combined with BDMC increased the ratio of Bak/Bcl-2 for leading to cell apoptosis. The Bax/Bcl-2 ratio was concerned with cell response to apoptotic signals (Rezaei et al, 2019).…”
Section: F I G U R Ementioning
confidence: 99%
“…In order to find out whether complex 1 would be effective against a human tumor lineage, we used HeLa cells. Complex 1 proved to be a potent apoptosis inducer in tumor cells, as it was observed in many other copper complexes that exhibit this property 22 , 29 , 32 , 61 , 62 , which is the safest mechanism of action of a drug, since apoptosis is a controlled event 30 . The genomic DNA degradation event triggered by complex 1 is believed to be the responsible for the induction of apoptosis, as described by other authors 22 , 31 , 45 .…”
Section: Discussionmentioning
confidence: 77%
“…Generally, cells that suffer double- or single-strand breaks in DNA are paralyzed in the G0/G1 or G2 phases 60 . Several copper complexes exhibit the ability to degrade tumor cell DNA 22 , 61 , 62 , and such ability was detected in complex 1 . The damage on DNA is believed to be responsible for this cell cycle arrest.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that copper complexes can induce cell death by promoting DNA double-strand breaks. In the study by Rezaei et al , [ 74 ] Cu (II) complex was found to induce apoptosis in HEPG2 cells by up-regulating the expression of tumor suppressor gene P53 and apoptosis genes ( BAX and Caspase - 8 ) and down-regulating the expression of anti-apoptosis gene BCL-2 . Some novel copper complexes have also been developed for the photodynamic therapy (PDT) of HCC.…”
Section: Role Of Copper Homeostasis Imbalance In Occurrence and Devel...mentioning
confidence: 99%